Development of Student Worksheets with Guided Inquiry Oriented on Reaction Rate Materials to Improve the Ability of Scientific Literacy of Pharmaceutical Vocational Students - S. Zahrah; M. Mitarlis (Universitas Negeri Yogyakarta, 2023)
This study intends to describe the feasibility of student worksheets with guided inquiry-oriented reaction rate materials to improve the ability of scientific literacy of pharmaceutical vocational students. Development research methods using 4D methods defining, designing, developing, and disseminating with limited only to the developing stage. The limited test was conducted on 22 students of class XI Pharmacy Vocational High School Bina Husada Pamekasan. Instruments in this study include study sheets, validation sheets, response questionnaires and observation sheets of learner activity, and pretest post-test sheets. The results showed that the feasibility of the student worksheet developed, which is suitable for use, includes the validity of the student worksheet in terms of aspects of content, presentation, language, and graphics, obtaining consecutive percentages of 78%, 78%, 90%, and 93% with valid / very valid categories. The practicality of the student worksheets developed is practically used by reviewing the results of student responses of 98% and the results of observation of student activities by 93% with very practical categories. The effectiveness of student worksheets developed effectively by looking after learning obtained a percentage of 100% with the complete category and an average N-gain score of 0.73 with a high category.